Penggunaan Platform Akademik Untuk Meningkatkan Publikasi Karya Ilmiah; Evaluasi Kinerja Dosen STIE Ganesha - Adi Wicaksono; Aep Saefullah; Hendra Candra; Moh Tahang (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This study aims to analyze the use of Google Scholar, SINTA, and BIMA platforms in improving the quality and quantity of academic publications as indicators of lecturer performance evaluation at the Ganesha College of Economics (STIE). The research was conducted for three months from February to April 2023. The method used a qualitative approach with a case study involving 67 lecturers of S1 Management, S1 Accounting and S2 Management of STIE Ganesha. Data collection techniques through literature studies, interviews, and observations. Data analysis was carried out using descriptive and comparative analysis techniques. The results showed that 45 permanent lecturers of STIE Ganesha had used the academic platform, namely Google Scholar and SINTA. And 67 other people already have a BIMA account. The obstacles of lecturers include a) Lack of awareness of lecturers in research, b) Research intention and interest are still weak, c) Do not understand how to use academic platforms, d) Technical ability to make research articles is not the same. The solution to anticipate it by: a) Providing training, socialization or technical support for lecturers in the use of academic platforms, b) Providing intensive assistance to lecturers every time in Writing Academic Skills. The role of the STIE Ganesha Research and Community Service Institute (LPPM) as an institution that handles lecturer research is very important in encouraging an increase in the publication of scientific papers by lecturers. The research limits the scope of the use of academic platforms for STIE Ganesha lecturers, it is hoped that wider research development can be carried out related to the publication of scientific papers by lecturers. This research contributes to knowledge insights for the general public in the use of academic platform tools. The research results are expected to provide input for educational institutions to improve the lecturer performance evaluation system and provide better support for improving the quality and quantity of lecturers' academic publications.